A Framework for Movement Analysis of Tasks: Recommendations From the Academy of Neurologic Physical Therapy's Movement System Task Force. Issue 9 (21st June 2021) - Quinn, Lori; Riley, Nora; Tyrell, Christine M; Judd, Dana L; Gill-Body, Kathleen M; Hedman, Lois D; Packel, Andrew; Brown, David A; Nabar, Nikita; Scheets, Patricia
Abstract: The American Physical Therapy Association's Vision Statement of 2013 asserts that physical therapists optimize movement in order to improve the human experience. In accordance with this vision, physical therapists strive to be recognized as experts in movement analysis. However, there continues to be no accepted method to conduct movement analysis, nor an agreement of key terminology to describe movement observations. As a result, the Academy of Neurologic Physical Therapy organized a task force that was charged with advancing the state of practice with respect to these issues, including the development of a proposed method for movement analysis of tasks. This paper presents the work of the Task Force, which includes (1) development of a method for conducting movement analysis within the context of the movement continuum during 6 core tasks (sitting, sit to stand, standing, walking, step up/down, and reach/grasp/manipulate); (2) glossary of movement constructs that can provide a common language for movement analysis across a range of tasks: symmetry, speed, amplitude, alignment, verticality, stability, smoothness, sequencing, timing, accuracy, and symptom provocation; and (3) recommendations for task and environmental variations that can be systematically applied. The expectation is that this systematic framework and accompanying terminology will be easily adapted to additional patient or client-specific tasks, contribute to development of movement system diagnostic labels, and ultimately improve consistency across patient/client examination, evaluation, and intervention for the physical therapy profession. Next steps should include validation of this framework across patient/client groups and settings.